Extranodal classical Hodgkin lymphoma involving the spinal cord: case report and review of the literature - Katell Le Dû; Nicolas Alarion; Hassan Rabi; Olivier Casasnovas; Philippine Robert; Amandine Durand; Bénédicte Burlet; Claire Tabouret-Viaud; Selim Ramla; Laurent Martin; Cédric Rossi (CNS Oncology, 2022)
Primary CNS involvement is very rare in Hodgkin lymphoma. Here we present two cases of spinal cord dissemination. Two women of 40 and 65 years of age presented symptoms of spinal cord injury; imaging showed an intramedullary mass in T10 and T2, respectively, without vertebral involvement and upper diaphragmatic lymph nodes. Lymph-node biopsy confirmed the diagnosis of classical Hodgkin lymphoma in both patients. The first patient received four cycles of chemotherapy (escalated BEACOPP and ABVD) with intrathecal therapy, and the second four cycles of doxorubicin, vinblastine, dacarbazine (AVD) and local irradiation after surgery decompression. Complete metabolic response was obtained at the end of treatment. After 5 and 7 years of follow-up respectively, neurological deficits persisted in both.